Development of Live Worksheet Based on Project-Based Learning to Promote Creative Thinking and Ecopreneurship on Biotechnology Concepts - Avinni Achmad, Annisa; Zulfiani, Zulfiani; Solihin, Solihin (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
This study aimed to develop teaching materials, one of which is student worksheets integrated with technology based on the project-based learning model to promote creative thinking and ecopreneurship on the concept of biotechnology at senior high school. The research used the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Field trials of live worksheet development were conducted at a high school in Bekasi, Indonesia with a sample of 25 10th-grade students. The results obtained from the validity test were 86.33% (very valid), the results of the creative thinking questionnaire were 83% (creative), the results of the ecopreneurship questionnaire were 78% (high), and the response results were 77%-85% (good to very good). Live worksheets improve the understanding of biotechnology material and promote creative thinking and ecopreneurship skills.